Prarancangan Pabrik Trisodium Fosfat Dari Asam Fosfat, Sodium Karbonat Dan Sodium Hidroksida Kapasitas 35.000 Ton Per Tahun - Susanti, Ratna Dwi; , Ir. Nur Hidayati, M.T., Ph.D; , Hamid Abdillah, S.T., M.T (2017)
Trisodium phosphate plant with capacity productionof 35,000 tons/year is planned to operated for 330 days/year, which will be established in Gresik, East Java.Trisodium phosphate production process is produced with four reactors, reactor RATB (R-120) and (R-121) to react sodium carbonate and phosphoric acid with conversion reaction of 99%, where in the reactor (R-130) and (R-131) are enabled for reacting disodium phosphate with sodium hydroxide with a conversion reaction 99.8%. Trisodium phosphate production as much as 4,419.1919 kg/hour, required phosphoric acid as much as 2.287.9682 kg/hour, sodium carbonate as much as 1,248.0101 kg/hour and sodium hydroxide as much as 920.28 kg/h. The supporting unit processes (utilities) include provision of water cooling 57,775.49 kg/hour, water steam 3,054.3387 kg/hour. Trisodium phosphate plant need power of 746.014 Kw which is supplied from PLN and a generator set as a backup. Compressed air requirement is30 m3/hour.Economic analysis of trisodium phosphate plant shows a profit before tax is Rp 60,252,913,141 per year and after tax profit reached Rp 42,177,039,199 per year. Percent Return On Investment (ROI) before tax15.14% and after-tax 10.60% respectively. Pay Out Time (POT) before tax 3.98 year and after tax year 4.85 years. Break Even Point (BEP) is 57.29% and Shut Down Point (SDP) is 24.86% and IRR is about19,67%. Feasibility analysis of trisodium phosphate plant can be concluded that the plant is profitable and viable to set up.